Portraits of Influential Chinese Educators - Hayhoe, Ruth. author. aut Link
XVIII, 398 p.
Keywords: This book conveys an understanding of China’s educational development from within. It does so through portraits of eleven influential educators whose ideas have shaped the educational reforms initiated by Deng Xiaoping in 1978. These eleven educators are portrayed in the context of their cultural heritage, families, communities and schools, offering their own deeply reflective interpretations of Chinese education. The book provides glimpses into the educational context of China’s recent move onto the world stage.